Peran Kepemimpinan Transformasional dan Budaya Organisasi dalam Membentuk Kinerja Karyawan di PT Sumber Bintang Rejeki - Hilda Mila Selfiani Bali; Tri Maryani (Mahesa Research Center, 2026)
This study aims to analyze the role of transformational leadership and organizational culture in shaping employee performance at PT Sumber Bintang Rejeki. The study employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation involving company leaders, supervisors, and employees selected through purposive sampling. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. The findings indicate that transformational leadership enhances employee motivation, responsibility, and engagement through open communication, clear direction, and attention to individual development. Organizational culture, characterized by the values of teamwork, discipline, responsibility, and openness, also contributes to creating a conducive and productive work environment. Furthermore, the synergy between transformational leadership and organizational culture strengthens employee commitment, improves productivity, and supports the effective and sustainable achievement of organizational goals. This study implies that strengthening transformational leadership, supported by a positive organizational culture, is an important strategy for improving employee performance.